Ayurvedic Management of Breast Fibroadenoma: A Case Report - Dr. Divya Vijay Shingare; Prof. (Dr.) Manjusha Karkare (The Bioscan, 2026)
Introduction: Fibroadenoma is a benign breast tumor commonly seen in women, characterized by a painless, mobile lump. While conventional treatments often involve surgical excision, Ayurvedic treatments offer a holistic approach targeting the root causes of the condition. This case report focuses on the Ayurvedic management of a patient with fibroadenoma, utilizing herbal remedies and lifestyle modifications.